(untitled) (Journal of Hama University, 2024)
Summary The aim of this research, in general, is to study the most important factors affecting the adoption of greenhouses by farmers in the Talkalakh region in Syria, using the method of binary logistic regression, as the dependent variable is a binary variable that takes the value (1) (farmers adopting greenhouses), and the value (0). (Farms do not adopt greenhouses), and is affected by two types of independent variables (continuous and categorical). The data was collected through a questionnaire distributed to a random sample of 376 farmers from Talkalakh region. The data was analyzed by the spss statistical analysis program, and the results showed: The logistic regression model fit the green house adoption data by classifying farmers into adopters and non-adopters, with a valid classification rate of 94.4% for the proposed model. The factors affecting the adoption of greenhouses are the age of the farmer, the farmer’s membership in a cooperative association or organization, the ease of the farmer obtaining a loan in case of need, the farmer’s knowledge of the recommendations for establishing greenhouses and dealing with them, and the quality of services provided by agricultural extension.